2019
DOI: 10.1177/1074248419882923
|View full text |Cite
|
Sign up to set email alerts
|

What Are Optimal P2Y12 Inhibitor and Schedule of Administration in Patients With Acute Coronary Syndrome?

Abstract: Guidelines recommend treatment with a P2Y12 platelet adenosine diphosphate receptor inhibitor in patients undergoing elective or urgent percutaneous coronary intervention (PCI), but the optimal agent or timing of administration is still not clearly specified. The P2Y12 inhibitor was initially used for its platelet anti-aggregatory action to block thrombosis of the recanalized coronary artery or deployed stent. It is now recognized that these agents also offer potent cardioprotection against a reperfusion injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…These observations were contrary to the findings from pre-clinical animal experiments demonstrating that early exposure of ticagrelor has pleiotropic cardioprotective effects that attenuate myocardial infarct size following coronary occlusion and reperfusion [138], to a greater degree than clopidogrel [139,140]. This has implications for the choice of initial antiplatelet agent in the management of STEMI patients [141]. It has been observed that the enteric absorption of ticagrelor is often delayed in STEMI patients, especially when opiates such as morphine are coadministered for pain relief [76][77][78][79].…”
Section: Ticagrelor In St-elevation Myocardial Infarctionmentioning
confidence: 62%
See 1 more Smart Citation
“…These observations were contrary to the findings from pre-clinical animal experiments demonstrating that early exposure of ticagrelor has pleiotropic cardioprotective effects that attenuate myocardial infarct size following coronary occlusion and reperfusion [138], to a greater degree than clopidogrel [139,140]. This has implications for the choice of initial antiplatelet agent in the management of STEMI patients [141]. It has been observed that the enteric absorption of ticagrelor is often delayed in STEMI patients, especially when opiates such as morphine are coadministered for pain relief [76][77][78][79].…”
Section: Ticagrelor In St-elevation Myocardial Infarctionmentioning
confidence: 62%
“…Administration of a parenteral P2Y 12 inhibitor that reaches the circulation within minutes and prior to emergency PCI could potentially optimise the salvage of ischaemic myocardium and minimise reperfusion injury, in addition to providing early platelet inhibition to prevent stent thrombosis. Further work is therefore required to assess the benefit of intravenous cangrelor or subcutaneous selatogrel prior to stenting, followed by subsequent transition to oral ticagrelor [87,141,143,144].…”
Section: Ticagrelor In St-elevation Myocardial Infarctionmentioning
confidence: 99%
“…Furthermore, until now, clinicians never had sensitive nor highly speci c tools that would allow the ultra-early identi cation of OMI in the absence of a STEMI pattern. Such enhanced diagnostics can allow the design and implementation of prospective interventional trials to assess the therapeutic effectiveness of targeted interventions in this vulnerable group (e.g., early upstream P2Y 12 inhibitor administration, 54 emergent vs. delayed reperfusion therapy, 55 glucose-insulin-potassium infusion, 56 etc. ).…”
Section: Discussionmentioning
confidence: 99%
“…Careful selection of high-risk patients [11,12] and multitarget cardioprotective strategies may increase the protective potential [23,33]. Since intravenous cangrelor may have similar cardioprotective efficacy as ticagrelor, an alternative treatment strategy might be intravenous cangrelor infusion shortly prior to stenting followed by subsequent post-PCI transition to an oral agent [17].…”
Section: Discussionmentioning
confidence: 99%